Pengaruh Return on Asset, Current Ratio, Net Profit Margin, dan Total Asset Turn Over terhadap Nilai Perusahaan: Studi Empiris pada Perusahaan Sektor Properti dan Perumahan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Pratama Suhendro; Roza Fitriawati (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2026)
This study aims to analyze the effect of Return on Asset (ROA), Current Ratio (CR), Net Profit Margin (NPM), and Total Asset Turnover (TATO) on company value as measured by Price Book Value (PBV) in property and real estate sector companies listed on the Indonesia Stock Exchange for the 2019–2023 period. This research adopts a quantitative method with a causal associative approach. The data was obtained from the financial reports of eight companies that met the purposive sampling criteria. Data analysis was conducted using multiple linear regression with the help of SPSS software. The results show that, partially, ROA and CR have a significant negative effect on PBV, while NPM does not have a significant effect on PBV, and TATO has a significant negative effect on PBV. Simultaneously, all four independent variables significantly affect PBV, with an R² value of 12.3%, indicating that most of the PBV variations are explained by other factors outside the research model. These findings provide insights for investors and company management regarding the importance of asset management and operational efficiency in enhancing firm market value.